Investigation on different materials after pulsed high field conditioning and low-energy H- irradiation - Serafim, C.; Peacock, R.; Calatroni, S.; Djurabekova, F.; Fontenla, A. T. Perez; Wuensch, W.; Sgobba, S.; Grudiev, A.; Lombardi, A.; Sargsyan, E.; Ramberger, S.; Bellodi, G. (Frontiers in Physics, 2024)
During operation the RFQ (Radio-Frequency-Quadrupole) of the LINAC4 at CERN is exposed to high electric fields which can lead to vacuum breakdown. It is also subject to beam loss that can cause surface modification, including blistering, which can result in reduced electric field holding and an increased breakdown rate. First experiments to study the high-voltage conditioning process and electrical breakdown statistics have been made using pulsed high-voltage DC systems in order to identify materials with high electric field handling capability and robustness to low-energy irradiation. In this paper we discuss the results obtained for the different materials tested. To complement these, an investigation of their metallurgical properties using advanced microscopic techniques was done, to observe and characterize the different materials and to compare results before and after irradiation and breakdown testing.